PENGARUH DOSIS INOKULUM AZOLLA DAN PUPUK FOSFAT ALAM TERHADAP KETERSEDIAAN P DAN HASIL PADI DI ALFISOL - Canggih Jati Nusantara; Sumarno Sumarno; Widyatmani Sih Dewi; Sudadi Sudadi (Universitas Sebelas Maret, 2014)
Rice production in Indonesia can not cover the national needs. The low productivity caused by the decline in soil fertility. One way to increase the phosphorus content in the soil is to provide natural phosphate fertilizer and Azolla inoculum. This study was conducted to determine the proper dose of Azolla inoculum and rock phosphate to increase the availability of phosphate and increase the yield of rice plants on land Alfisol. This study uses the two-factor factorial CRD comparative treatment of manure and fertilizer N, P, K. Analysis of the observed data using analysis of variance at 5% level and if there is a significant difference effect followed by DMRT 5% level to compare between treatments. The results showed that treatment of Azolla inoculum and phosphate can increase the availability of phosphate in the Alfisol soil and can increase rice yield. On the parameters available P showed the highest results in the treatment of Azolla 2.5 tons / ha without natural phosphate and Azolla 5 tons / ha of natural phosphate 350 kg / ha which is 10.81 ppm. In addition, administration of Azolla inoculum and phosphate levels give rise to CEC, organic matter, total N in the soil and soil pH.